Bilateral Florid Papillomatosis of the Nipple: An Unusual Indicator for Metachronous Breast Cancer Development—A Case Report. (30th December 2013) - Sasi, Walid; Banerjee, Dibyesh; Mokbel, Kefah; Sharma, Anup K.
Abstract : Adenoma or florid papillomatosis of the nipple (FPN) is a rare benign disease which has histopathological features similar to those of a mammary papillary carcinoma. Here, we report a rare case of bilateral florid papillomatosis of the nipple and breast cancer, with a literature review.